2022
DOI: 10.5194/acp-22-917-2022
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol formation from the oxidation of decamethylcyclopentasiloxane at atmospherically relevant OH concentrations

Abstract: Abstract. Decamethylcyclopentasiloxane (D5, C10H30O5Si5) is measured at parts per trillion (ppt) levels outdoors and parts per billion (ppb) levels indoors. Primarily used in personal care products, its outdoor concentration is correlated to population density. Since understanding the aerosol formation potential of volatile chemical products is critical to understanding particulate matter in urban areas, the secondary organic aerosol yield of D5 was studied under a wide range of OH concentrations and, correspo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…Representative error bars indicate ±1σ uncertainty in binned SOA yield values, ±50% uncertainty in OH exp exposure values, and ±70% uncertainty in Cl exp exposure values. Additional figure notes: a Wu and Johnston, b Janechek et al, c Charan et al, d Han et al, 1 Cl generated using OFR369-iCl 2 under humid conditions, 2 Cl generated using OFR369-iCl 2 under dry conditions, and 3 Cl generated using OFR254/313-iC 2 Cl 2 O 2 under dry conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Representative error bars indicate ±1σ uncertainty in binned SOA yield values, ±50% uncertainty in OH exp exposure values, and ±70% uncertainty in Cl exp exposure values. Additional figure notes: a Wu and Johnston, b Janechek et al, c Charan et al, d Han et al, 1 Cl generated using OFR369-iCl 2 under humid conditions, 2 Cl generated using OFR369-iCl 2 under dry conditions, and 3 Cl generated using OFR254/313-iC 2 Cl 2 O 2 under dry conditions.…”
Section: Resultsmentioning
confidence: 99%
“…First, we characterized the yield and chemical composition of SOA obtained from OH oxidation of D 5 and compared our results to previous studies. 14,16,22 OFRs use residence times that are on the order of minutes and oxidant concentrations that are typically 100−1000 times higher than ambient levels. Their ability to access photochemical aging time scales of up to several days was critical in previous studies examining D 5 + OH SOA formation as a result of the relatively long OH lifetime of D 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of VCPs to ambient OA is not fully understood and only limited modeling studies have been reported (Mohr et al, 2015;Vlachou et al, 2018;Pennington et al, 2021;Qin et al, 2021;Seltzer et al, 2021). Additionally, few experimental and chamber studies of VCPs have been conducted with limited characterization of aerosol products Johnston, 2016, 2017;Harrison and Well, 2012;Charan et al, 2020Charan et al, , 2021Humes et al, 2022). For example, the analysis of SOA from the oxidation of cyclic methyl siloxanes Johnston, 2016, 2017;Fu et al 2020;Alton and Browne, 2020;Charan et al, 2021) and cyclic siloxanes (Janechek et al, 2019) has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, few experimental and chamber studies of VCPs have been conducted with limited characterization of aerosol products Johnston, 2016, 2017;Harrison and Well, 2012;Charan et al, 2020Charan et al, , 2021Humes et al, 2022). For example, the analysis of SOA from the oxidation of cyclic methyl siloxanes Johnston, 2016, 2017;Fu et al 2020;Alton and Browne, 2020;Charan et al, 2021) and cyclic siloxanes (Janechek et al, 2019) has been conducted. Kinetic studies with limited products characterization have been reported for the oxidation of benzyl alcohol (BnOH) by hydroxyl radicals (Bernard et al, 2013;Wang, 2015;Well, 2009, 2012).…”
Section: Introductionmentioning
confidence: 99%